Penerapan Analisis Berbasis Fraktal dalam Klasifikasi Citra Retakan pada Permukaan Jembatan Beton - Muchtar, Mutmainnah; Sutoyo, Muhammad Nurtanzis; Paliling, Alders; Sunyanti, Sunyanti; Iin, Johar Nur (Universitas Indraprasta PGRI Jakarta, 2024)
Bridge cracks are gaps that form on the concrete surface of the bridge due to the aging process or the load exceeding its capacity. Knowing the cracks in the bridge is very important because undetected cracks can cause serious damage to the bridge structure, threaten the safety of road users, and increase the cost of maintaining and repairing infrastructure. Fractal analysis is a mathematical approach that studies structures and patterns in complex and irregularly shaped objects. This study aims to apply fractal-based analysis using fractal dimension and lacunarity features in classifying image cracks on the surface of concrete bridges. By using fractal analysis and the K-Nearest Neighbor classifier, this study succeeded in achieving an accuracy of crack image classification on concrete bridges of 97.6%, followed by precision and recall values of 97.659% and 97.6%. These results prove the potential of fractal analysis as an effective method for detecting cracks in concrete bridges and can make an important contribution to the maintenance and safety of bridge infrastructure in the future.